Impact of donor dopamine on immediate graft function after kidney transplantation - Schnülle, Peter; Yard, Benito A.; Braun, Claude; Domínguez Fernández, Emilio; Schaub, M.; Birck, Rainer; Sturm, J.; Post, Stefan; Woude, Fokko J. van der (American journal of transplantation, 2004)
Optimizing medical donor management may have a considerable impact on transplantation outcome. This study investigated the effect of donor dopamine on initial graft function in renal allograft recipients, involving 254 consecutive recipients of a cadaver kidney, aged 18-74 years, transplanted between 1990 and 2003. Immunosuppression was based on cyclosporine. Patients were grouped according to donor use of dopamine during intensive care. Delayed graft function (DGF), and serial creatinine concentrations were compared between the groups. Dopamine-treated and -untreated donors were very similar regarding hemodynamics and renal function. Delayed graft function occurred in 47/158 treated and 48/96 untreated kidneys (p = 0.001). Donor dopamine was associated with a more rapid decrease of s-creatinine, which became obvious on the first postoperative day. Of patients in the treated and untreated group, respectively, 81.9% and 65.8% reached a s-creatinine level less than 2 mg/dL during the first month (p = 0.005). Donor dopamine remained predictive of a normalized s-creatinine level [HR 1.71; 95% CI 1.22-2.41] after controlling for confounding factors by multivariate Cox regression. Donor dopamine is associated with improvements of initial graft function after kidney transplantation. The beneficial effect of dopamine is achievable without side-effects for the recipients, and correlates with superior long-term graft survival.
Gesehen am 31.05.2022